2011
DOI: 10.1177/0898010111423422
|View full text |Cite
|
Sign up to set email alerts
|

Unaccompanied Hospitalized Children

Abstract: Pediatric nurses dealt with increased emotional work while remaining compassionate with their patients. Nurses indicated that they needed to understand their own life-worlds and that parents' day-to-day contingencies may affect parents' ability to remain with their hospitalized children. Participants were aware of judgmental attitudes which could interfere with the development of therapeutic relationships with parents, and therefore, with hospitalized children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…A study of nurses' perception of unaccompanied hospitalized children suggested that nurses were concerned about their patients' safety during the absence of their parents. The nurses were placed in a difficult situation by having to put toddlers into cribs to keep them safe, which caused them to feel sorry for the child or by placing the child on a regular bed with a high risk of fall (Roberts, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of nurses' perception of unaccompanied hospitalized children suggested that nurses were concerned about their patients' safety during the absence of their parents. The nurses were placed in a difficult situation by having to put toddlers into cribs to keep them safe, which caused them to feel sorry for the child or by placing the child on a regular bed with a high risk of fall (Roberts, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Roberts (2010) revealed that one-third of hospitalized children were not accompanied by their parents for at least part of the hospitalisation. A qualitative follow-up study was conducted, and it was discovered that financial issues and not being able to leave work were the main reasons for not being with the child in the hospital (Roberts, 2012). These findings contrast with typical Indonesian hospitals where a guardian must stay with the hospitalized child.…”
Section: Methodsmentioning
confidence: 98%
“…Nurses reported feelings of guilt and distress when having to implement necessary interventions that caused children fear, pain, or distress (Livesley, 2005;Roberts & Messmer, 2012). Nurses worried about children's safety in the hospital alone, parents' ability to care for their child when discharged, and the negative effects of being a child alone (Roberts & Messmer, 2012). Some nurses tried to empathize with absent parents, while many judged them; almost all nurses believed a parent should accompany a hospitalized child (Roberts & Messmer, 2012).…”
Section: Nurses' Perceptionsmentioning
confidence: 99%
“…Nurses worried about children's safety in the hospital alone, parents' ability to care for their child when discharged, and the negative effects of being a child alone (Roberts & Messmer, 2012). Some nurses tried to empathize with absent parents, while many judged them; almost all nurses believed a parent should accompany a hospitalized child (Roberts & Messmer, 2012).…”
Section: Nurses' Perceptionsmentioning
confidence: 99%
See 1 more Smart Citation